2016
DOI: 10.1007/s11306-016-1076-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel plasma biomarker of atenolol-induced hyperglycemia identified through a metabolomics-genomics integrative approach

Abstract: Introduction While atenolol is an effective antihypertensive agent, its use is also associated with adverse events including hyperglycemia and incident diabetes that may offset the benefits of blood pressure lowering. By combining metabolomic and genomic data acquired from hypertensive individuals treated with atenolol, it may be possible to better understand the pathways that most impact the development of an adverse glycemic state. Objective To identify biomarkers that can help predict susceptibility to bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Over the past decade, pharmacogenomics studies have identified several promising genetic signatures associated with variability in response to thiazide diuretics . Additionally, pharmacometabolomics has been successful in identifying novel pathways and biomarkers influencing patients’ variability in response to different drugs . Recently, using an untargeted metabolomics approach, we were able to identify several novel metabolites significantly associated with the BP response to HCTZ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, pharmacogenomics studies have identified several promising genetic signatures associated with variability in response to thiazide diuretics . Additionally, pharmacometabolomics has been successful in identifying novel pathways and biomarkers influencing patients’ variability in response to different drugs . Recently, using an untargeted metabolomics approach, we were able to identify several novel metabolites significantly associated with the BP response to HCTZ .…”
Section: Introductionmentioning
confidence: 99%
“…7,10,11 Additionally, pharmacometabolomics has been successful in identifying novel pathways and biomarkers influencing patients' variability in response to different drugs. [12][13][14] Recently, using an untargeted metabolomics approach, we were able to identify several novel metabolites significantly associated with the BP response to HCTZ. 15 Also, pharmacolipidomics represents a promising approach to identify novel biomarkers of drug response and yield mechanistic insights for several drugs.…”
mentioning
confidence: 99%
“…Recently we found that b-alanine was increased after beef intake compared with fish because of a high amount of b-alanine in beef mince compared with fish (17), suggesting that b-alanine may reflect beef intake. Other studies have linked b-alanine and carnosine (b-alanine conjugated with the amino acid histidine) with T2D, which may also explain this result (43)(44)(45).…”
Section: Discussionmentioning
confidence: 91%
“…Pharmacometabolomics and pharmacogenomics were combined to discover that purine pathway enzymes and genes were involved in the variation of patients' response to aspirin [75]. The pharmacometabolomics and pharmacogenomics combined approach revealed that β-alanine and rs2669429 may be predictors of atenolol-induced hyperglycaemia [92]. The broad utility of the concept that pharmacometabolomics informs pharmacogenomics has been demonstrated in a series of related studies [78,[81][82][83][84][85][86].…”
Section: Pmx Data and Pgx Datamentioning
confidence: 99%